Organisational impact on evaluating training return on investment - Subaashnii,; Thilageswary,; Komathi,; Priya, (2012)
Training is one of a great deal matter in human resource development activities. The benefits of a training program conducted can be seen at a very simplified level to a complex stage. Thus, the complex stage of identify the training outcome will be at the organizational results. In order to identify the return from the training invested on organization impact, evaluating return on investment is seemed to be a challenge. The study identifies the models involved in evaluating ROI for training. Further, the importance and the challenges also examined.